Niagara@ catheter equipped with a novel helical flow inducer to improve hemodynamic performance - Yang, Yang; Yan, Hao; Xianli, Huang; Maoxia, Ran; Chen, Liu; Zhuang, Liu; Yu, Chen; Ling, Zhang (Frontiers in Bioengineering and Biotechnology, 2025)
Hemodialysis is an important means to sustain life in patients with end-stage renal disease In China, more than 100,000 hemodialysis patients need to have a catheter fitted at least once (temporary or long term) for dialysis. Despite the widespread use and low cost of HD catheters, they remain prone to critical issues such as high thrombosis rates, infections, and dysfunction. This study addresses the persistent challenge of thrombosis formation in dialysis catheters by investigating the incorporation of helical flow inducers, a strategy inspired by the naturally occurring helical blood flow in arterial systems. In this research, helical flow inducers with varying pitch and diameter were integrated into the widely used Niagara@ catheter. Computational fluid dynamics simulations were conducted to evaluate the impact on key parameters such as local normalized helicity (LNH), residence time (RT), shear stress, and flow velocity. The results demonstrated that 1) small-diameter inducers produce helical flow. Among inducers with identical diameter, those with a smaller thread pitch are more likely to induce increased LNH; 2) a small thread pitch helical flow inducer reduced the percentage of blood volume, with RT exceeding 0.015 s from 40.8% in the control to 12.7%, suggesting a substantial reduction in thrombosis risk; 3) the study also found that the introduction of small thread pitch helical flow inducers led to increased shear stress, with Model A showing an average shear stress of 49.2 Pa, compared to 32.0 Pa in the control. This highlights the need for careful optimization to balance the benefits of reduced thrombosis risk with the potential for shear-induced hemolysis. In conclusion, the integration of helical flow inducers into dialysis catheters offers a promising strategy for improving intraluminal flow dynamics and reducing the risk of thrombosis.